Pengaruh Good Corporate Governance dan Environmental, Social, Governance Terhadap Nilai Perusahaan (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di BEI Periode Tahun 2020-2023) - Roudhotun Ni’mah; Rohmawati Kusumaningtias (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to empirically test the effect of Good Corporate Governance (GCG), which is proxied by the audit committee and managerial ownership, and Environmental, Social, and Governance (ESG), which is proxied by environmental, social, and governance performance, on company value represented by Price to Book Value (PBV). The data for this study were obtained from the financial statements of 324 companies listed on the Indonesia Stock Exchange (IDX) during the period 2020-2023. Data analysis was carried out using descriptive statistical methods, classical assumption tests, and normality tests with the help of SPSS software. The results of the study indicate that the ESG variable as a whole does not have a significant effect on company value. In contrast, the GCG variable was found to have a significant effect on company value. This finding indicates that the implementation of good governance through the existence of an audit committee and effective managerial ownership can increase company value. However, environmental, social, and governance performance as measured in the ESG framework has not shown a significant role in influencing company value. This research contributes to the development of literature on the relationship between GCG, ESG, and corporate value, and serves as a reference for corporate management and investors in making strategic decisions based on good governance.